Notoginsenoside R1 promotes MC3T3-E1 differentiation by up-regulating miR-23a via MAPK and JAK1/STAT3 pathways - Chunsheng Wang; Huanwei Sun; Yiming Zhong (Artificial Cells, Nanomedicine, and Biotechnology)
Growing evidence have probed a stimulatory influence of Notoginsenoside R1 (NGR1) with osteoblastic probability. miR-23a plays a crucial role in osteoblast differentiation. Whereas whether there exists a miRs-related mechanism by which NGR1 promotes preosteoblast differentiation remains unexplored. We pre-treated MC3T3-E1 with NGR1 to anatomize Runx-2 and Osx expression as well as ALP activity. Phosphorylation of regulators was evaluated by Western blot. SB203580 and Ruxolitinib were used to reduce the phosphorylation of regulators. The effects of NGR1 on miR-23a were verified by qRT-PCR. We analyzed the expression of Runx-2 and Osx, ALP activity as well as phosphorylation of regulators in MC3T3-E1 stimulated with NGR1 and transfected with miR-23a inhibitor. We found that NGR1 enhanced Runx-2 and Osx expression as well as ALP activity in a concentration-dependent manner. NGR1 might exhibit an efficacious promotion on Runx-2, Osx and ALP activity by increased phosphorylation of MAPK, JAK1, and STAT3. NGR1 resulted in miR-23a overexpression which positively modulated Runx-2 and Osx expression as well as ALP activity. Our results showed that miR-23a inhibitor reduced the phosphorylation of MAPK, JAK1 and STAT3 in MC3T3-E1 pre-treated with NGR1. In conclusion, NGR1 exhibited an efficacious promotion on preosteoblast differentiation by up-regulating miR-23a through MAPK and JAK1/STAT3 pathways.Highlights:NGR1 induces MC3T3-E1 differentiation;miR-23a is positively regulated by NGR1;NGR1 regulates MAPK/JAK1/STAT3 through miR-23a.